A) (-6) + (-8)
7- (-3)
(-14) - 6
9 - 12
B) (-3) - 10
(-11) - (-9)
(-8) - (-7)
(-9) - 2
C) 13 - (-13)
(-40 - (-40)
(-22) - 40
(-53 - 30
D) (-60) - (-30)
(-180) - 20
710 - (-10)
(-150) - (-200)
PROSZE NA TERAZ!!!


Odpowiedź :

Odpowiedź:

A)   (-6) + (-8) =   -6 - 8 = - 14

    7- (-3)= 7 +3= 10

   (-14 ) -6= -14 - 6 = - 20

     9 - 12 = - 3

B)    (-3) - 10= -3 - 10 = - 13

      (-11 ) - (-9)= - 11 +9 = - 2

      (-8) - (-7 )= - 8 +7 = - 1

     ( - 9 ) - 2= -9 - 2 = - 11

C)   13 - (-13 ) = 13 +13= 26

     (-40) - (-40)=   - 40 +40 = 0

     ( - 22 - 40= - 22 - 40 = - 62

    ( -53) -30= - 53 - 30 = - 83

D)    (-60)- (-30)= - 60 +30 = - 30

         (- 180)- 20= - 180 - 20 = - 200

      710 - (-10)= 710+10= 720

        (-150)- (-200)= - 150 + 200= 50

Szczegółowe wyjaśnienie: